Radiation dosimetry of (18)F-AzaFol: A first in-human use of a folate receptor PET tracer - Gnesin, Silvano (EJNMMI Res, 2020)
BACKGROUND: The folate receptor alpha (FRα) is an interesting target for imaging and therapy of different cancers. We present the first in-human radiation dosimetry and radiation safety results acquired within a prospective, multicentric trial (NCT03242993) evaluating the (18)F-AzaFol (3′-aza-2′-[(18)F]fluorofolic acid) as the first clinically assessed PET tracer targeting the FRα. MATERIAL AND METHODS: Six eligible patients presented a histologically confirmed adenocarcinoma of the lung with measurable lesions (≥ 10 mm according to RECIST 1.1). TOF-PET images were acquired at 3, 11, 18, 30, 40, 50, and 60 min after the intravenous injection of 327 MBq (range 299–399 MBq) of (18)F-AzaFol to establish dosimetry. Organ absorbed doses (AD), tumor AD, and patient effective doses (E) were assessed using the OLINDA/EXM v.2.0 software and compared with pre-clinical results. RESULTS: No serious related adverse events were observed. The highest AD were in the liver, the kidneys, the urinary bladder, and the spleen (51.9, 45.8, 39.1, and 35.4 μGy/MBq, respectively). Estimated patient and gender-averaged E were 18.0 ± 2.6 and 19.7 ± 1.4 μSv/MBq, respectively. E in-human exceeded the value of 14.0 μSv/MBq extrapolated from pre-clinical data. Average tumor AD was 34.8 μGy/MBq (range 13.6–60.5 μGy/MBq). CONCLUSIONS: (18)F-Azafol is a PET agent with favorable dosimetric properties and a reasonable radiation dose burden for patients which merits further evaluation to assess its performance. TRIAL REGISTRATION: ClinicalTrial.gov, NCT03242993, posted on August 8, 2017